Quantification of respiratory effort magnitude in spontaneous breathing patients using Convolutional Autoencoders. (March 2022) - Ang, Christopher Yew Shuen; Chiew, Yeong Shiong; Vu, Lien Hong; Cove, Matthew E
Highlights: Current methods of quantifying the magnitude of spontaneous breathing effort are highly invasive. A machine learning model is developed to quantify magnitude of spontaneous breathing effort. Model is trained using simulated spontaneous breathing and normal breathing flow waveforms. Clinical data analysis using the model yields a median spontaneous breathing magnitude of 25.39% amongst the patient cohort. Potential for real-time monitoring of patient-ventilator interaction. Abstract: Background: Spontaneous breathing (SB) effort during mechanical ventilation (MV) is an important metric of respiratory drive. However, SB effort varies due to a variety of factors, including evolving pathology and sedation levels. Therefore, assessment of SB efforts needs to be continuous and non-invasive. This is important to prevent both over- and under-assistance with MV. In this study, a machine learning model, Convolutional Autoencoder (CAE) is developed to quantify the magnitude of SB effort using only bedside MV airway pressure and flow waveform. Method: The CAE model was trained using 12, 170, 655 simulated SB flow and normal flow data (NB). The paired SB and NB flow data were simulated using a Gaussian Effort Model (GEM) with 5 basis functions. When the CAE model is given a SB flow input, it is capable of predicting a corresponding NB flow for the SB flow input. The magnitude of SB effort (SBEMag ) is then quantified as the difference between the SB and NB flows. The CAE model was used to evaluate the SBEMag of 9 pressure control/ support datasets. Results were validated using a mean squared error (MSE) fitting between clinical and training SB flows. Results: The CAE model was able to produce NB flows from the clinical SB flows with the median SBEMag of the 9 datasets being 25.39% [IQR: 21.87–25.57%]. The absolute error in SBEMag using MSE validation yields a median of 4.77% [IQR: 3.77–8.56%] amongst the cohort. This shows the ability of the GEM to capture the intrinsic details present in SB flow waveforms. Analysis also shows both intra-patient and inter-patient variability in SBEMag . Conclusion: A Convolutional Autoencoder model was developed with simulated SB and NB flow data and is capable of quantifying the magnitude of patient spontaneous breathing effort. This provides potential application for real-time monitoring of patient respiratory drive for better management of patient-ventilator interaction.